ALGORITHM FOR AUTOMATIC COMPENSATION OF VOLTAGE DIPS IN POWER SUPPLY OF INDUSTRIAL FACILITIES - Malarev, Vadim; Bogdanov, Ivan; Senchilo, Nikita (Journal of Applied Engineering Science, 2020)
The factors of failures and their impact on the equipment of large enterprises is discussined in this article. The optimal method for compensating voltage dips was selected and the principle of operation of the developed compensator operation algorithm is described. According to the algorithm, a model was developed at the MatLab Simulink environment. The graphs of the model are presented.